2007
DOI: 10.1002/pssb.200572707
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the influence of the orientation and fibre reinforcement on the Negative Poisson's ratio in composite laminates

Abstract: PACS 62.20.Dc, 81.05.ZxThe variation of through-thickness Poisson's ratio with fibre type and orientation has been investigated using a specially developed Fortran program. Glass fibre/epoxy resin composites were always found to be conventional, but negative Poisson's ratio values of up to ν 13 = -0.746 were produced over certain orientation angles for Kevlar and carbon reinforcements. This underlines the need for anisotropic pre-preg material. A range of [± β/± θ] s angles were investigated for carbon fibre l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 11 publications
2
22
0
Order By: Relevance
“…A first experimental evidence of the enhanced damage tolerance characteristics of NPR through-the-thickness laminates has been provided by Alderson et al [21]. These experimental results confirm the potential of using high-end laminate composites with sinclastic curvature [22] and high NPR effect using special stacking sequences [23]. In this work, the theoretical approach of Ogden and Vinh is used for incompressible anisotropic solids [15], and applied to 3D crossply laminates as per Clarke et al [20] exhibiting throughthe-thickness NPR behaviour.…”
supporting
confidence: 63%
“…A first experimental evidence of the enhanced damage tolerance characteristics of NPR through-the-thickness laminates has been provided by Alderson et al [21]. These experimental results confirm the potential of using high-end laminate composites with sinclastic curvature [22] and high NPR effect using special stacking sequences [23]. In this work, the theoretical approach of Ogden and Vinh is used for incompressible anisotropic solids [15], and applied to 3D crossply laminates as per Clarke et al [20] exhibiting throughthe-thickness NPR behaviour.…”
supporting
confidence: 63%
“…So, carbon fibre has been the preferred reinforcement and prediction of suitable stacking sequences has been carried out along with basic experimental work to verify the Poisson's ratio [5,13,[15][16][17]. It should be noted that work has also been reported on producing negative Poisson's ratios in Kevlar laminates [18] and filament wound tubes [19] and one study has reported a negative in-plane Poisson's ratio in glass fibre laminates [20].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis is based on the theory of elastic anisotropic plates that could be found in many reference books, and the full formulation of the problem can be also found in the previous work of the authors [19], as well as in Herakovich [7]. In what follows, N x and N y represents, respectively, the axial load in the x and in the y direction.…”
Section: Theoretical Formulations Of the Problem And Basic Equationsmentioning
confidence: 99%
“…Various types of composites carbon/epoxy are used to validate the results obtained in literature [7,19]. We are currently lacking specific experimental results on the through-the-thickness NPR of these laminates.…”
mentioning
confidence: 97%